Living with a diagnosis of Placenta Accreta Spectrum: Mothers' and Fathers' experience of the antenatal journey and the birth. - Helena C Bartels; Antje Horsch; Naomi Cooney; Donal J Brennan; Joan G Lalor (PLoS ONE, 2023)
Objective Much research into Placenta Accreta Spectrum (PAS) has focussed on the associated maternal morbidity and mortality. However, mothers' and fathers' lived experiences of the aftermath of a diagnosis of PAS up to the birth and beyond has received little attention. Therefore, the aim of this study was to increase our understanding of the psychological consequences of PAS on women and their partners during pregnancy, up to and including the birth. Methods In-depth interviews were conducted with 29 participants; 6 couples were interviewed together (n = 12), 6 couples were interviewed separately (n = 12), and 5 women were interviewed without their partner. Data from the antenatal and intrapartum periods are presented. Couples were eligible for inclusion if they had a diagnosis of PAS within the previous 5 years. An Interpretative Phenomenological Analysis approach was used to gather and analyse data. Virtual interviews were conducted over a 3-month period from February to April 2021. Results Themes emerged relating to two distinct timepoints, the antenatal period and birth. The antenatal period had two main themes: the first antenatal main theme was "Living with PAS", which had two sub-themes: "Lack of knowledge of PAS" and "Experiences of varied approaches to care". The second antenatal main theme was "Coping with uncertainty", which had two sub-themes of "Getting on with it", and "Emotional toll". Relating to birth, two main themes emerged. The first main theme was "A traumatic experience", with three sub-themes of "Saying goodbye", "Experiencing trauma" and the "Witnessing of trauma" (by fathers). The second main theme which emerged was "Feeling safe in the hands of experts", with two subthemes of "Safety in expert team" and "Relief at surviving". Conclusions This study highlights the significant psychological consequences a diagnosis of PAS has on mothers and fathers, how they try to come to terms with the diagnosis and the experience of a traumatic birth, and how management within a specialist team can alleviate some of these fears.